MSME Performance Strategy Post Covid-19 Pandemic Through The Implementation Of Innovations And Strategic Decisions: Systematic Literature Review (SLR) - Amelia Setyawati; Iradah Rahman; Adelia Rahma; Farij Ibadil Maula (Pusat Riset dan Inovasi Nasional, 2023)
One place for students who want to learn about entrepreneurship through After the Covid-19 Pandemic caused high environmental pressure to occur. One of them occurred in the increasingly uncertain sector of the country's economy. There are many things that can be done to provide economic solutions, one effective way is through improving the performance of MSMEs. Micro, Small and Medium Enterprises (MSMEs) have important characteristics in economic development, both in developing and developed countries. The importance of the role of MSMEs in helping the country's economy, it is hoped that the longer the development of MSME performance will increase. The strategy decision emerged as a response to the current decline in MSME graphics performance, with steps. Strategic planning in small companies is much more informal compared to large businesses, however, MSMEs must continue to develop new missions, goals, strategies and policies, to then compare external opportunities and threats with their potential strengths and weaknesses. In this study MSME innovation as an additional stimulus because innovation is thought to increase competitive advantage, understanding the relationship between performance and innovation in micro, small and medium enterprises can help the company's competitive strategy. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals. related to keywords. Based on the literature study conducted, it was found that the strategic decisions made by MSME actors were still not quite right, on average MSME actors made short-term strategic decisions. Meanwhile, the innovation of MSME actors is very qualified to have a competitive advantage and competitiveness. The results of the research have implications for the first two things in the behavior of MSMEs, it is hoped that they will continue to improve their abilities creatively, innovatively and adaptively, both parties the government is expected to continue to improve and equip MSMEs facilities evenly and improve mentoring programs / training for MSMEs.